Integrasi Kurikulum Merdeka dan Pendidikan Islam: Studi Kasus di MI Munzalam Mubaroka Bulukerto - Miftaku Ni’amah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The transformation of the national curriculum through the implementation of the Independent Curriculum requires educational institutions, including madrasas, to adapt without losing their Islamic identity. This study aims to explore how MI Munzalam Mubaroka Bulukerto integrates the Independent Curriculum with Islamic education in the context of learning and curriculum management. The research employed a qualitative approach with a case study method. Data collection techniques included participatory observation, in-depth interviews, and documentation with the madrasah principal, teachers, students, and parents. The results show that the madrasah successfully combined the principles of the Independent Curriculum—such as differentiated learning and the Pancasila student profile project—with Islamic values ​​through a thematic approach and a project based on akhlaqul karimah (good moral values). The madrasah principal acted as the driving force behind the integration, while teachers became creative actors in developing contextual, religious-based teaching modules. The study's conclusions confirm that the integration of the national curriculum and Islamic education is not only possible but can also serve as a model for developing a unique madrasah curriculum. This research contributes to the development of integrative curriculum practices in private madrasahs based on local values ​​and contexts.